Industrial product service systems: a guideline for the development of service-oriented manufacturing enterprise groups. Issue 1 (28th March 2011) - Jiang, Pingyu; Mu, Hui
On the basis of analysing the changes of product and enterprise organisational structure figures, in this paper, we introduce the conceptual framework of industrial product service systems (iPSS) and their roles for enterprises to promote their manufacturing modes from traditional one to service-oriented one. Furthermore, the fundamental scientific issues and correspondent key enabling technologies are presented in detail. It is pointed out that the iPSS would bring new chances for 'Made-in-China' and is also a guideline for China enterprises to develop themselves into new service-oriented manufacturing enterprise groups.